Expert views on state-level naloxone access laws: a qualitative analysis of an online modified-Delphi process - Sean Grant; Rosanna Smart (BMC, 2022)
Abstract Background Expanding availability to naloxone is a core harm reduction strategy in efforts to address the opioid epidemic. In the US, state-level legislation is a prominent mechanism to expand naloxone availability through various venues, such as community pharmacies. This qualitative study aimed to identify and summarize the views of experts on state-level naloxone access laws. Methods We conducted a three-round modified-Delphi process using the online ExpertLens platform. Participants included 46 key stakeholders representing various groups (advocates, healthcare providers, human/social service practitioners, policymakers, and researchers) with expertise naloxone access laws. Participants commented on the effectiveness and implementability of 15 state-level naloxone access laws (NALs). We thematically analyzed participant comments to summarize views on NALs overall and specific types of NAL. Results Participants commented that the effectiveness of NALs in reducing opioid-related mortality depends on their ability to make sustained, significant impacts on population-level naloxone availability. Participants generally believed that increased naloxone availability does not have appreciable negative impacts on the prevalence of opioid misuse, opioid use disorder (OUD), and non-fatal opioid overdoses. Implementation barriers include stigma among the general public, affordability of naloxone, and reliance on an inequitable healthcare system. Conclusions Experts believe NALs that significantly increase naloxone access are associated with less overdose mortality without risking substantial unintended public health outcomes. To maximize impacts, high-value NALs should explicitly counter existing healthcare system inequities, address stigmatization of opioid use and naloxone, maintain reasonable prices for purchasing naloxone, and target settings beyond community pharmacies to distribute naloxone.